Application of low molecular weight heparin on immunoglobulin (IG) A，IgG , IgM, prothrombin time (PT), thrombin time (TT), fibrinogen (FIB), and activated partial thrombokinase time (APTT) , tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleuk: biomarkers in hyperlipidemic acute pancreatitis - Lu, Yujie; Zhu, Xinchao; Wen, Caixia; Zhang, Qiang; Zhao, Li; Ling, Jia (Journal of Medical Biochemistry, 2025)
Objective: To explore the impact of low molecular weight heparin (LMWH) on serum immunoglobulin (IG) A，IgG , IgM, prothrombin time (PT), thrombin time (TT), fibrinogen (FIB), and activated partial thrombokinase time (APTT) , tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-8 (IL-8) in hyperlipidemic acute pancreatitis (HLAP) patients.Methods: One hundred HLAP patients treated in our hospital from January 2022 to December 2024 were divided into control group (CG) and experimental group (EG). The CG accepted conventional therapy and routine nursing. Based on the conventional therapy and routine nursing, the EG accepted LMWH therapy and early enteral nutrition nursing. The recovery status and changes of various indicators were compared in 2 groups.Results: Relative to CG, EG had higher total effective rate, shorter disappearance time of abdominal distension and abdominal pain, exhaust recovery time, defecation recovery time, bowel sound recovery time and length of hospitalization, lower serum amylase and urine amylase levels, better improvements of blood lipid markers, better improvements of coagulation function indexes, lower levels of inflammatory markers, higher levels of nutritional indexes, higher levels of immune indexes and lower incidence of complications.Conclusion: LMWH combined with early enteral nutrition nursing is effective in the management of HLAP patients, which can promote physical recovery of patients, improve coagulation function and inflammatory response, promote nutritional status and immune function, and reduce the incidence of complications.